DAMPAK PERKEMBANGAN PARIWISATA TERHADAP KONDISI SOSIAL BUDAYA DAN LINGKUNGAN DI DESA CANGGU: DAMPAK PERKEMBANGAN PARIWISATA TERHADAP KONDISI SOSIAL BUDAYA DAN LINGKUNGAN DI DESA CANGGU - Anjeli Wahyuningtyas, Ni Wayan; Susianti, Hartanti Woro (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Canggu is one of the areas that has experienced rapid development in the tourism sector. Canggu Village has become a leading tourist destination in Badung Regency, alongside Kuta and Nusa Dua. The development of tourism in Canggu Village has shown significant changes that affect socio-cultural conditions as well as the environment. This study aims to identify the positive and negative impacts of tourism development on the socio-cultural conditions of the local community and on environmental conditions in Canggu Village. This research employs a quantitative approach with descriptive analysis. The sampling technique used was proportional sampling and purposive sampling, involving 100 respondents. Data were collected through a survey using questionnaires, supported by interviews to strengthen the data, as well as documentation. The results indicate that the most significant positive socio-cultural impact perceived by the community is the emergence of a sense of pride in local products and cultural arts that are appreciated by tourists. Meanwhile, the most significant positive environmental impact is the implementation of waste management activities resulting from tourism development in Canggu Village. On the other hand, the community also perceives negative impacts, including the modification of local arts to attract increasing tourist visits, as well as environmental impacts, particularly traffic congestion.